James Brooke And His Attempts To Instill British Power In Sarawak In The 19th Century - M. Dien Madjid (Institut Agama Islam Sumatera Barat, 2023)
This paper attempts to prove the hard work James Brooke put into enhancing his influence in Sarawak around the nineteenth century. This period signified British exploration conducted on the Malay Peninsula and its vicinity. Brooke clutched the opportunity to attempt his luck in Sarawak. His efforts were difficult, considering that he had to compete with the Sultanate of Brunei and the Head of the Dayak tribe to reach the highest helm. The historical sources got are based on several books published during the Brooke dynasty era in Sarawak. Of course, other secondary sources are also used to contribute to the historical analysis. Historical research methods were used to process this working paper so that it becomes a text worthy of discussion of similar themes. Memories of colonialism in Sarawak are essential to discuss in this era, bearing in mind that there were several positive values that can be treasured, which are then transformed into ideas for Sarawak's development as a sovereign territory. The memory of history will fill an essential space that reduces nationalism and awareness without sacrificing the interests of the public.